BaTiO3 nanotubes by co-axial electrospinning: Rheological and microstructural investigations. Issue 4 (April 2020) - Hedayati, Mehdi; Taheri-Nassaj, Ehsan; Yourdkhani, Amin; Borlaf, Mario; Zhang, Jian; Calame, Michel; Sebastian, Tutu; Payandeh, Seyedhosein; Clemens, Frank Jörg
Abstract: BaTiO3 (BT) nanotubes (NTs ) were synthesized using a co-axial electrospinning process. BT precursor/PVP-ethanol and heavy mineral oil were used as the shell solution and core liquid, respectively. The rheological studies indicated that NTs could be formed by a stable jet at a range of viscosities of the shell solution. Due to the shear thinning behavior of the shell solutions, their actual viscosity values at the time of jet formation will be lower than the viscosity of the core liquid. The morphology of the obtained NTs was strongly influenced by the viscosity of the shell solution. By increasing the concentration of BT precursor, the morphology of the BT NTs was changed from porous to more dense structure. XRD analysis revealed that the crystallization of BT NTs occurs at 550–630 °C calcination temperature range. Raman spectra confirmed the presence of tetragonal phase at early stage of crystallization.